Vascular plant, bryophyte, and lichen biodiversity of Agguttinni Territorial Park, Baffin Island, Nunavut, Canada: an annotated species checklist of a new Arctic protected area - Lynn J. Gillespie; Paul C. Sokoloff; Geoffrey A. Levin; Jennifer Doubt; R. Troy McMullin (Check List, 2024)
Agguttinni Territorial Park is a large, newly established park on the east-central coast of Baffin Island in Nunavut, Canada. Previous knowledge of the plant and lichen biodiversity was limited and based mostly on collections made during the 1950 Baffin Island Expedition. We conducted a ﬂoristic inventory of the park in 2021 and re-examined previous collections. We recorded 141 species of vascular plants belonging to 25 families, 69 species of bryophytes in 27 families, and 93 species of lichens in 23 families. Most of the vascular plant and bryophyte species are new records for the park area, and some vascular plants, bryophytes, and lichens are newly reported for Baffin Island, Nunavut, or the Canadian Arctic or represent signiﬁcant range extensions. Vascular plant species diversity varied greatly among localities, with inland valleys at the heads of ﬁords showing highest diversity and interior rocky barrens showing the lowest.